DETEKSI THORIUM PADA KAOS LAMPU PETROMAKS MENGGUNAKAN SPEKTROMETER BETA DENGAN DETEKTOR SINTILASI DARI BAHAN ORGANIK NAFTALEN - Nina GInanto Putri; Evi Setiawati (Youngster Physics Journal, 2015)
The radioactivity of Thorium contained in gas mantles has been successfully detected. Thorium is the source of radiation that it emits the types of alpha (α) and beta (β) radiation, so it can be said to have radiation with little activity. In this study, the detection of radioactivity of Thorium using a scintillation detector with an organic material of Naphthalene scintillator which has a efficiency value of 53.42%. In addition, the composition of the materials was characterized by Energy Dispersive X-ray spectroscopy (EDX). Gas mantles mounted on petromaks lights and it turned on. The result of combustion of powders was pressurized, so that it became a solid sample. The variations of  sample were A and B, while there were 9 variations of Naphthalene scintillator thickness of 0.5 mm intervals in the range 1-5 mm. The A sample result of EDX characterization show that the composition of the constituent material C, Mg, Cu, and Th. The composition of the material making up the B sample  was  B, O, Y, Pt, Pb, and Th. Thorium activity was determined by counting the samples for 10 seconds each variation of the thickness of the scintillator. The radiation activities of Thorium were found in A and B samples respectively, 8.419 and 8.692 nCi.Keywords: Plasma jet, characterization of  plasma jet,  flow rate of Argon gas, voltage, current